Multidimensional strategic outlook on global competitive energy economics and finance - Dinçer, Hasan; Yüksel, Serhat (Emerald Publishing Limited, 2022)
Economical energy supply is vital for a country's financial success, and factors such as price, continuity, environmental pollution and the country's own energy resources are important contributors. Multidimensional Strategic Outlook on Global Competitive Energy Economics and Finance analyses current trends in energy production and use, with a focus on technological developments that contribute to the reduction of price in energy production and renewable energy sources that provide continuity in energy production and do not emit carbon into the atmosphere. Expanding on the current literature, this book focuses purely on current issues that can increase energy efficiency, while proposing strategies to use energy more effectively and efficiently. The strategies presented in this book will be a significant guide to both academics and industry professionals.